UK competition judgements 1950-2005 - Ashton, John K. (UK Data Service, 2015)
A compilation of the scale, nature and focus of competition cases examined and reported by the UK competition authorities 1950-2005. This includes both 'market' and 'merger' cases and includes a summary of the key business issues raised in each case. The ESRC Centre for Competition Policy (CCP) at the University of East Anglia (UEA) undertakes interdisciplinary research into competition policy and regulation that has real-world policy relevance without compromising academic rigour. It prides itself on the interdisciplinary nature of the research and the members are drawn from a range of disciplines, including economics, law, business and political science. The Centre was established in September 2004, building on the pre-existing Centre for Competition and Regulation (CCR), with a grant from the ESRC (Economic and Social Research Council). It currently boasts a total of 26 faculty members (including the Director and a Political Science Mentor), 4 full- and part-time researchers and 23 PhD students.